1997
DOI: 10.1007/s11627-997-0042-6
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ventilation rate on proliferation and hyperhydricity of Dianthus caryophyllus L

Abstract: Comparative studies of carnation micropropagation under four different ventilation rates showed that using gas-permeable filters, with gelled or liquid media and modifying the volume of culture medium, it was possible to establish a suitable hydric state to obtain good proliferation rates with gelled and liquid medium, as well as optimal acclimatization of microcuttings. The following parameters were measured: ventilation rate, gas exchange coefficients, relative water loss, increase of agar concentration, mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0
3

Year Published

1998
1998
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 45 publications
4
31
0
3
Order By: Relevance
“…3). Hyperhydricity induced by lack of ventilation is described for several in vitro-cultured plants (McCown and Sellmer, 1987;Smith and McClelland, 1991;Debergh et al, 1992) and, particularly, in other D. caryophyllus cultivars in our previous reports (Majada et al, 1997(Majada et al, , 2000Fal et al, 1999). However, total hyperhydricity was induced only in 'Pink Calypso' explants cultured in jam jars with metal caps (the lowest E and desiccation), but not in the other cultivars (Table 3).…”
Section: In Vitro Physical Environment Effectsmentioning
confidence: 75%
See 3 more Smart Citations
“…3). Hyperhydricity induced by lack of ventilation is described for several in vitro-cultured plants (McCown and Sellmer, 1987;Smith and McClelland, 1991;Debergh et al, 1992) and, particularly, in other D. caryophyllus cultivars in our previous reports (Majada et al, 1997(Majada et al, , 2000Fal et al, 1999). However, total hyperhydricity was induced only in 'Pink Calypso' explants cultured in jam jars with metal caps (the lowest E and desiccation), but not in the other cultivars (Table 3).…”
Section: In Vitro Physical Environment Effectsmentioning
confidence: 75%
“…Our previous results (Majada et al, 1997(Majada et al, , 2000Fal et al, 1999) showed differences between some Dianthus caryophyllus L. cultivars in their behavior when cultured in vessels ventilated through porous membrane closures. This ventilation system was adequate for improving micropropagation when hyperhidricity was a problem.…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…O tipo de fechamento dos recipientes é outro fator de controle da UR. O uso de tampas com filtros de 0.2μm (MAJADA et al, 1997), ou de membranas permeáveis ao ar associadas, ou não, a sistema de ventilação forçada (ZOBAYED et al, 2001), são exemplos de alternativas para controlar a UR e evitar a hiperidricidade. O emprego de meio líquido associado a sistemas de aeração permite evitar a hiperidricidade e aumentar a taxa de micropropagação (DANTAS et al, 2001).…”
Section: Alternativas De Controleunclassified